Expired atorvastatin drug as corrosion inhibitor for mild steel in hydrochloric acid solution - Singh P.; Chauhan D.S.; Srivastava K.; Srivastava V.; Quraishi M.A. (My University, 2025)
The application of expired drugs as corrosion inhibitors provides a cost effective and environmentally benign alternative to otherwise tedious and costly disposal/degradation process. In this context, we herein investigate the use of expired atorvastatin (EA) for corrosion inhibition of mild steel in 1 M HCl solution using weight loss, electrochemical impedance spectroscopy (EIS), and potentiodynamic polarization (Tafel) methods. Fresh atorvastatin (FA) drug was also used for above studies for comparison purpose to understand whether there is any significant difference between the inhibition efficiency of the two after the expiration date of the drug. EIS analysis shows an increase in polarization resistance due to the adsorbed inhibitor molecules on metal surface. Potentiodynamic polarization indicates that both the EA and FA act as mixed-type inhibitors but predominantly behave as cathodic inhibitors. The adsorption of EA and FA on mild steel surface follows the Langmuir adsorption isotherm. SEM shows a smoother surface of mild steel in the presence of FA and EA drug in acidic solution. Both the fresh drug and its expired counterpart showed almost similar results in all the studies, thereby verifying the validity of the expired atorvastatin drug as a novel and efficient corrosion inhibitor for mild steel. © 2017, The Author(s).